Wykorzystanie Internetu w rozwijaniu autonomii ucznia – wyniki badania ankietowego - Kruk, Mariusz (Neofilolog, 2010)
The aim of the article is to show the extent to which the use of the Internet resources promotes the development of learner autonomy among Polish senior high school learners of English. The data were gathered by means of a questionnaire before and after the treatment and subjected to quantitative and qualitative analysis. It should be noted that the data came from a larger research project in which two groups, experimental and control, received different types of instruction. More precisely, the learners in the experimental group gained access to the Internet and exercised more freedom in learning. On the other hand, the control group students were taught in a traditional way. The results indicate that the experimental learners became more autonomous than their control counterparts.